Determination of the Fault Zone by the Level of Short-Circuit Currents - F. A. Romaniuk; E. V. Buloichyk; M. A. Shevaldin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The methods of determination the fault zone according to the parameters of the emergency mode, which can be used to improve the performance of technical perfection of current protection lines of distributive 6–10 kV one-way power networks, are considered. The advantage of the algorithm of determination the zones of short circuit (SC) according to the level of emergency currents as compared to the remote unilateral method addressing the parameters of the damaged loop corrupted loops (loops) is noted. Calculation of the estimated distance to the point of SC on the basis of difference of damaged phase currents has been proposed, that enables the independence of the obtained result on the type of the fault. A technique for increasing the reliability of the method for determination the short-circuit zone by the level of emergency currents based on information about the type of damage has also been proposed. The effect of load currents and contact resistances of different levels on the magnitude and nature of the changes in the errors of the calculated distance to the short circuit was investigated by the method of computational experiment. The levels of contact resistances relative to the total resistance of the line depending on the place of SC occurrence are determined that provides reliable determination of the fault zone; it is demonstrated that the nature of their alteration is approximately the same for lines of medium and long length. The expediency of correction of the calculated distance to the fault location in many cases of short circuits through the contact resistance so to improve the protection capacity of the high-speed current protection stage is demonstrated. Based on the results of the computational experiment, correction factors for the correction of the value of the emergency current have been obtained; on the basis of the latter the fault zone is determined. The estimation of efficiency of the proposed method of correction has been carried out; it is shown that its application makes it possible to improve the accuracy of determination the fault zone and to expand the zone of instantaneous shutdown of short circuit. The dynamic properties of the proposed algorithm for different modes of the line operation have been investigated; it is ascertained that, in the worst case, the determination of the short circuit zone for a time not exceeding 27 ms is provided.